Jakarta Smart City Governace: Policy, Actors and Financing - Wiwit Widodo; Gumilar Rusliwa Somantri; Athor Subroto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aims to investigate how Jakarta Smart City is managed from a policy, actor and funding perspective. Jakarta, which is currently not the nation's capital, is trying to transform into a business center and global city through the Jakarta Smart City strengthening initiative to realize a smart city 4.0 ecosystem that accommodates synergy between residents and the city government. Jakarta Smart City governance is the key to achieving the ideals of smart city development that contributes to improving the quality of life of its residents. This study is an inductive study using an exploratory descriptive approach. Data collection methods are carried out by literature reflection, analysis of planning and regulatory documents, and in-depth interviews with city officials, practitioners, and academics. The findings show that the development of smart cities in Indonesia cannot be separated from two levels of policy, namely the central government policy level that supports the national smart city program including digital transformation, especially in terms of providing digital infrastructure, and the city government policy level which turns out to be more complex in managing the smart city ecosystem both within the city government and also towards public services. The relationship between actors in the smart city ecosystem is important in shaping the digital space of Jakarta Smart City. In terms of findings, the findings show the need to develop innovative schemes in financing the initiation of smart city projects.